Academic inbreeding and intellectual contributions in Chile - Sergio Zuniga-Jara (Multidisciplinary Business Review)
Existing literature shows that academics trained at the same university where they are employed generally exhibit lower academic achievement levels than their colleagues trained at other universities. However, the general validity of this reasoning has recently been questioned. In this line, our results show that the mean level of academic inbreeding in business and economics in Chilean universities is high, with a mean level of 46.4%, quite different from the mean for universities in western countries. We found that for the two top-ranked Chilean universities, some degree of cross-academic inbreeding among them seems justiﬁed, at least temporarily. In the other Chilean universities, we observed a statistically signiﬁcant inverse relationship between academic inbreeding and intellectual contributions. This suggests that self-limitation of inbreeding appears to be highly recommended for most Chilean universities, as it is for the majority of the world’s top-ranked universities.